Factors That Influence Fraud Heptagon Theory On Financial Statements Fraud (Empirical Study on the Mining Sector Listed on the Indonesia Stock Exchange for the Period 2018-2022) - Ranny Ariany Djami; Murtanto Murtanto (Publikasi Indonesia, 2024)
This research was conducted on Mining Sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The purpose of this study was to determine the effect of Fraud Heptagon Theory on Financial Statement Fraud using the F-Score Model partially and simultaneously. This study used quantitative methods, namely data obtained from secondary data in the form of annual reports. The sample in this study were 25 mining sector companies on the Indonesia Stock Exchange with a purposive sampling method. The data analysis used is data panel regression using the Eviews 12 application program. The results of the research on partially, pressure and ignorance has an effect on financial statement fraud, while opportunity, rationalization, competence, arrogance, and greed have no effect on financial statement fraud. Simultaneously, pressure, opportunity, rationalization, competence, arrogance, ignorance, and greed have no effect on financial statement fraud